Simulation of A Buck-Boost DC-DC Converter for Battery Starter and Battery Storage in Fuel Cell Power System - Alias, Mohamad Amir Amirul; Wahyu Mulyo Utomo, (Evolution in Electrical and Electronic Engineering, 2022)
A buck-boost DC-DC converter is used to control the charge current and discharge of the battery. In a buck mode, the converter will charge the battery while in boost mode it will discharge the battery using a voltage from the fuel cell. Components include a DC power source (in this case, a fuel cell), controlled switches, diodes, inductors and capacitors. This converter uses to investigate which battery is best to use while the battery is being charged and discharged. Based on the result achieved, it shows that each battery has the own their own advantages and disadvantages when using this buck-boost DC-DC converter.